Marjan F1: A Semi-Determinate Tomato Hybrid Exhibiting High Yield Potential and Improved Resistance to Diseases - Nadeem, Kashif; Sardar, Sadia; Iqbal, Mudassar; Hammad, Ghazanfar; Ali, Atif; Sardar, Ayesha; Anjum, Maria; Iqbal, Muhammad (Integrative Plant Biotechnology, 2025)
The development of locally adapted, disease-tolerant and high-yielding semi-determinate tomato hybrids is an emerging focus in agricultural research of Pakistan. These hybrids are designed to address challenges such as disease resistance, particularly against fungal and viral infections, while ensuring high productivity coupled with suitable fruit traits and adaptability to environmental conditions. In Punjab, determinate, indeterminate and semi-determinate tomatoes are cultivated, however, their production is heavily reliant on plant protection measures, making cultivation both costly and largely confined to farmers’ fields. Marjan F1, a semi-determinate tomato hybrid was developed with a fair degree of tolerance against fungal diseases, making it well-suited for open-field cultivation. Its resistance enables cultivation with reduced dependence on plant protection inputs. Additionally, Marjan F1 is highly suitable for kitchen gardening, as it can be cultivated with minimal plant protection measures, thereby allowing home gardeners to grow it organically. In yield trials, Marjan F1 demonstrated a 3.98% yield advantage over three exotic check hybrids (TO-1057 F1, T-1359 F1 and TO-6242 F1). It showed resistance to late blight, gray mold and Fusarium wilt, while maintaining moderate resistance to early blight. Overall, Marjan F1 exhibited superior disease resistance compared to two exotic checks (TO-1057 F1 and TO-6242 F1), coupled with better yield performance.